2004
DOI: 10.1111/j.1365-2982.2004.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Vanilloid receptor 1 antagonists attenuate disease severity in dextran sulphate sodium‐induced colitis in mice

Abstract: Neurogenic mechanisms have been implicated in the induction of inflammatory bowel disease (IBD). Vanilloid receptor type 1 (TRPV1) has been visualized on nerve terminals of intrinsic and extrinsic afferent neurones innervating the gastrointestinal tract and local administration of a TRPV1 antagonist, capsazepine, reduces the severity of dextran sulphate sodium (DSS)-induced colitis in rats (Gut 2003; 52: 713-9(1)). Our aim was to test whether systemically or orally administered TRPV1 antagonists attenuate expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 54 publications
(71 reference statements)
3
116
0
Order By: Relevance
“…29,42 The present results corroborate these data by showing a great increase of CB2 mRNA expression in colonic tissue from DSS-treated mice, compared with colons from the control group ( Figure 6E). Of note, preventive oral treatment with BCP markedly diminished CB2 expression in colons from mice on day 7 after DSS treatment ( Figure 6E).…”
Section: Beneficial Effects Of ␤-Caryophyllene On Dss-induced Colitissupporting
confidence: 88%
See 4 more Smart Citations
“…29,42 The present results corroborate these data by showing a great increase of CB2 mRNA expression in colonic tissue from DSS-treated mice, compared with colons from the control group ( Figure 6E). Of note, preventive oral treatment with BCP markedly diminished CB2 expression in colons from mice on day 7 after DSS treatment ( Figure 6E).…”
Section: Beneficial Effects Of ␤-Caryophyllene On Dss-induced Colitissupporting
confidence: 88%
“…O'Sullivan et al 14 demonstrated that ⌬9-tetrahydrocannabinol causes vasorelaxation through activation of PPAR␥. Both CB2 and PPAR␥ agonists reduce MPO activity 29,69 and increase a T H 2 cytokine profile 68,70 in experimental colitis in mice. In addition, the activation of CB2 and/or PPAR␥ significantly reduces CXCL1/KC and MIP-2 tissue levels 71,72 and inhibits NF B, IKK␣/␤, and CREB activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations